Media image of sport volunteering during the UEFA Euro 2012™ and the motives for social work and its style of volunteers working in Poznan and in Poland - Brdak, Marek (Journal of Education, Health and Sport, 2015)
Brdak Marek. Media image of sport volunteering during the UEFA Euro 2012™ and the motives for social work and its style of volunteers working in Poznan and in Poland. Journal of Education, Health and Sport. 2015;5(11):533-541. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35693 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A533-541 http://pbn.nauka.gov.pl/works/684759 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Brdak Marek. Media image of sport volunteering during the UEFA Euro 2012™ and the motives for social work and its style of volunteers working in Poznan and in Poland. Quality in Sport. 2015;1(1):21-28. eISSN 2450-3118. http://ojs.ukw.edu.pl/index.php/QiS/article/view/QUALITY%20IN%20SPORT%201%20%281%29%202015%2C%20s.%2021-28 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Marek Brdak[1] University of Physical Education in Poznan Media image of sport volunteering during the UEFA Euro 2012™ and the motives for social work and its style of volunteers working in Poznan and in Poland Abstract Background: Volunteering in sport is the most popular and media form of pro-social work in Europe. In Poland, to such activity the conditions are still creating by the largest growth of numbers of institutions active in the public sector in the field of sport, recreation, tourism and hobbies. Interest in volunteering at sport events is increasing, especially among young people. The media image of sport volunteering is adopted by the organizer with chosen promotional strategy. The associated expectations of the participants, their motivation and style of behaving during participation in volunteer project as a consequence are also factors determining the media image of sport volunteering. Aim: The aim of the study is to compare the style of engaging in social work of their participants and motives of taking that kind of work by volunteers working in Poznan. Material and Method: The analysis included data available on the Internet regarding to organization of volunteer work during the UEFA Euro 2012™ in Poland and Ukraine as well as literature review regarding to the motivation to unpaid work in Poland. The motives of engaging in to volunteering as well as style of that work was compared between groups of participants of volunteering at UEFA Euro 2012™ in Poznan and Poland. Results: Volunteering at UEFA Euro 2012™ was separated on two areas, sports and urban and was coordinated by different organizers. The convergence between the motivational climate created by organizers of two independent volunteer projects at UEFA Euro 2012™ and motives for social work of its participants is visible. Encouraging volunteers to unpaid work in sport area of tournament by presenting it as a possibility to feel the sports atmosphere was similar to motives and significant more often reported by its volunteers than volunteers working in urban zone. Altruistic motives underlying in social activities significantly more often were reported by volunteers working in urban area of tournament where motivational climate was introduced as a possibility to feel the social dimension of tournament. Material profits of volunteering in both areas of tournament were significantly more often higher rated by volunteers working in the urban zone of tournament. Analysis of style of engaging in pro – social activity showed that volunteers working in sport zone of tournament significantly higher were involved in this type of work and significantly higher presents a regularity in this type of work. However experience in sport volunteering was the domain of volunteers working in urban zone. Conclusions: The implementation of the adopted strategy for creating the media image of the Official Volunteer Program at UEFA Euro 2012™ is related with motives for undertaking voluntary work of its participants. Motives for undertaking voluntary during UEFA Euro 2012™ as well as style of engaging in such work are different between volunteer working in different zones of tournament. Key words: motive, sport, volunteering, UEFA Euro 2012™. [1] mbrdak@awf.poznan.pl